A Sulfur‐Tolerant MOF‐Based Single‐Atom Fe Catalyst for Efficient Oxidation of NO and Hg0. Issue 20 (9th April 2022) - Yang, Weijie; Liu, Xiaoshuo; Chen, Xuelu; Cao, Yue; Cui, Shaoping; Jiao, Long; Wu, Chongchong; Chen, Chuanmin; Fu, Dong; Gates, Ian D.; Gao, Zhengyang; Jiang, Hai‐Long
Abstract: Catalytic oxidation of NO and Hg 0 is a crucial step to eliminate multiple pollutants from emissions from coal‐fired power plants. However, traditional catalysts exhibit low catalytic activity and poor sulfur resistance due to low activation ability and poor adsorption selectivity. Herein, a single‐atom Fe decorated N‐doped carbon catalyst (Fe1 ‐N4 ‐C), with abundant Fe1 ‐N4 sites, based on a Fe‐doped metal–organic framework is developed to oxidize NO and Hg 0 . The results demonstrate that the Fe1 ‐N4 ‐C has ultrahigh catalytic activity for oxidizing NO and Hg 0 at low and room temperature. More importantly, Fe1 ‐N4 ‐C exhibits robust sulfur resistance as it preferably adsorbs reactants over sulfur oxides, which has never been achieved before with traditional catalysts. Furthermore, SO2 boosts the catalytic oxidation of NO over Fe1 ‐N4 ‐C through accelerating the circulation of active sites. Density functional theory calculations reveal that the Fe1 ‐N4 active sites result in a low energy barrier and high adsorption selectivity, providing detailed molecular‐level understanding for its excellent catalytic performance. This is the first report on NO and Hg 0 oxidation over single‐atom catalysts with strong sulfur tolerance. The outcomes demonstrate that single‐atom catalysts are promising candidates for catalytic oxidation of NO and Hg 0 enabling cleaner coal‐fired power plant operations. Abstract : A single‐atom Fe catalyst (denoted Fe1 ‐N4 ‐C) is theoretically predicted and fabricated by controlled metal–organic framework pryrolysis for oxidation of NO and Hg 0, aiming at multipollutants removal in coal‐fired power plants. Strikingly, the Fe1 ‐N4 ‐C exhibits sulfur resistance in catalytic oxidation of NO and Hg 0, where SO2 boosts the catalytic cycle of NO oxidation over Fe1 ‐N4 ‐C through accelerating the regeneration of active sites.